2006
DOI: 10.1111/j.1540-6210.2006.00657.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Emotional Labor in Public Organizations: An Empirical Examination of the Link to Performance

Abstract: Chicago. She studies public personnel policies, the changing labor force, and occupational segregation by gender -the different ways that men and women fi nd jobs, the different expectations of women and men at work, and how workplace phenomena affect women and men differently. She is the author of Breaking Out of the Pink Collar Ghetto: Policy Solutions for Non-College Women (M. E. Sharpe, 2004).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
137
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(141 citation statements)
references
References 38 publications
0
137
0
4
Order By: Relevance
“…Previous research (Meier, Mastracci & Wilson 2006;Pierce, 1995) has found that display rules in organisations, that is the organisational expectations regarding the kind of emotions employees ought to express and suppress during interpersonal interactions in the workplace (Rafaeli & Sutton, 1987), can differ for males and females. The reported differences in emotional labour levels between the full-time and part-time university lecturers, was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research (Meier, Mastracci & Wilson 2006;Pierce, 1995) has found that display rules in organisations, that is the organisational expectations regarding the kind of emotions employees ought to express and suppress during interpersonal interactions in the workplace (Rafaeli & Sutton, 1987), can differ for males and females. The reported differences in emotional labour levels between the full-time and part-time university lecturers, was not significant.…”
Section: Discussionmentioning
confidence: 99%
“…Management scholars have linked emotions with several organizational variables, such as job performance, the quality of interpersonal relations, and the success of strategic judgment (Huy, 1999). In a similar vein, Public Administration literature has long emphasized the importance of emotions within public organizations (Brewer and Selden, 1998;Berman and West, 2008;Meier et al, 2006 …”
Section: Honesty-humility Emotionality and Agreeablenessmentioning
confidence: 99%
“…While much of the research has centered on the private service sector, there is also research on emotional labor in the provision of public services (Ogbonna & Harris, 2004;Robson & Bailey, 2009;Smith, 1992), and recent years have seen the emergence of studies with an explicit focus on emotional labor from the perspective of public administration (Guy and Newman, 2004;Guy, Newman & Mastracci, 2008;Hsieh, 2012;Hsieh & Guy, 2009;Hsieh, Jin & Guy, 2012;Hsieh, Yang & Fu, 2011;Jin & Guy, 2009;Mastracci, Newman & Guy, 2006;Meier, Mastracci & Wilson, 2006). Emotional labor scales have been applied to a range of public service providers, including child protection workers, corrections officials, and 911 call takers (Guy et al, 2008), a social service nonprofit (Hsieh & Guy, 2009), and workers handling complaints in the Florida Division of Consumer Services (Jin & Guy, 2009), as well as combinations of public service workers (Hsieh, 2012).…”
Section: Emotional Labor In Korean Local Government: Testing the Consmentioning
confidence: 99%